2022
DOI: 10.3390/brainsci12081080
|View full text |Cite
|
Sign up to set email alerts
|

Functional Relationship between Inhibitory Control, Cognitive Flexibility, Psychomotor Speed and Obesity

Abstract: In the last decades, it has been proposed that executive functions may be particularly vulnerable to weight-related issues. However, evidence on the matter is mixed, especially when the effects of sociodemographic variables are weighted. Thus, the current study aimed at further examining the relationship between executive functions and obesity. To this aim, we compared treatment-seeking overweight, obese, and morbidly obese patients with normal-weight control participants. We examined general executive functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 127 publications
1
18
0
4
Order By: Relevance
“…According to the “corticolimbic disconnection hypothesis” [ 147 , 148 ], fronto-limbic suppressive mechanisms would mediate an inhibitory response generating a state of emotional numbness. During depersonalization experiences, activation of the prefrontal cortex (PFC) interacts with the anterior cingulate cortex (ACC) and amygdala, generating low emotionality, attentive difficulties, autonomic mitigation, and indifference to pain [ 152 , 153 , 154 , 155 ]. In addition, hypoactivity of posterior parietal regions has been associated with deficits in processing and integrating somatosensory information [ 156 , 157 , 158 , 159 , 160 , 161 ] and low self-awareness.…”
Section: Discussionmentioning
confidence: 99%
“…According to the “corticolimbic disconnection hypothesis” [ 147 , 148 ], fronto-limbic suppressive mechanisms would mediate an inhibitory response generating a state of emotional numbness. During depersonalization experiences, activation of the prefrontal cortex (PFC) interacts with the anterior cingulate cortex (ACC) and amygdala, generating low emotionality, attentive difficulties, autonomic mitigation, and indifference to pain [ 152 , 153 , 154 , 155 ]. In addition, hypoactivity of posterior parietal regions has been associated with deficits in processing and integrating somatosensory information [ 156 , 157 , 158 , 159 , 160 , 161 ] and low self-awareness.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, decreased EFs have been associated with reduced food intake inhibition [ 12 , 13 , 14 ], high-fat food ingestion [ 15 ], lower appetite regulation [ 16 ], decreased energy expenditure [ 17 ], increased emotional eating [ 18 ], inability to learn from past experiences [ 19 ], delayed weight loss [ 12 ], poor adherence to healthy nutrition [ 20 , 21 ], and poor outcomes to weight loss interventions [ 22 ]. In line with these findings, some studies have found poor executive performance in patients with obesity [ 11 , 23 , 24 , 25 ]; furthermore, neuroimaging evidence exists on the relationship between decreased neural activity within the frontal cortex—the main cortical substrate of EFs—and obesity [ 26 , 27 , 28 ]. This evidence might be supported by studies finding a significant relationship between adipose tissue and systemic inflammation interacting with the physiology of the blood–brain barrier, likely affecting cognitive performance [ 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 77%
“…Still, we found that the motor domain played a non-negligible role in the dynamics of such a relationship. In a scientific context in which the link between EFs and obesity needs to be further investigated [ 11 , 16 , 23 , 24 , 25 , 103 , 104 ], these findings may contribute to extending the debate on the matter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been argued that EFs could predict body weight variability ( 18 , 25 ). For instance, EFs were found to be related with increased intake of high-fat foods ( 26 31 ), poor energy expenditure ( 32 ), increased susceptibility to emotional eating ( 33 ), inability to learn from past experiences ( 34 ), and worse outcomes in treatments aimed at weight decrease ( 27 , 35 ).…”
Section: Introductionmentioning
confidence: 99%